Software engineering aspects of continuous development and new paradigms of software production and deployment : first International Workshop, DEVOPS 2018, Chateau de Villebrumier, France, March 5-6, 2018, Revised selected papers /: first International Workshop, DEVOPS 2018, Chateau de Villebrumier, France, March 5-6, 2018, Revised selected papers. (2019) - Unknown
No abstract available